Harold, Marg, and the Boys: The Relevance of Class in Canadian History - Heron, Craig (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
AbstractClass has been a controversial category of historical analysis. Historians and social theorists have often attacked its relevance, but even those who find it a helpful way of understanding the past (and present) have had to deal with challenges from new theoretical perspectives, especially from those sensitive to gender and race. They have also had to recognize that there is no direct link between the material situation of members of a social class and their consciousness of their social situation. Diverse discourses emerge to give meaning to social experience, and are adopted, adapted, or rejected to varying degrees. This paper suggests that, after three decades of debate, we should now consider class formation as a fluid, dynamic process of social differentiation through which people’s lives are shaped by the pressures, constraints, and opportunities of their situation in relation to the means of production, the divisions of labour within patriarchy, and the racial distinctions in particular societies; but also one in which people negotiate their own understandings of the world and act on them. To illustrate this process at work, the paper discusses the lives of one working-class family in suburban Toronto from the 1940s to the 1970s and their engagement with new postwar social developments. They not only shaped distinctively working-class forms of gender, suburbanism, religion, ethnicity, citizenship, popular culture, meritocracy, and consumerism; but also wove all of those into a distinctively working-class identity.